Pseudomembranous colitis in a child - Sreenivasamurthy, Rajani Hassan; Doddaiah, Narayanappa Doddaiah; Nagaraj, Rashmi (Indian Journal of Child Health, 2018)
A 7-year-old male child with a history of fever of 1-month duration, treated with ceftriaxone for 10 days, developed foul-smelling bloody loose stools associated with severe abdominal cramps. Colonoscopy revealed yellowish-white pseudomembranes suggestive of pseudomembranous colitis which is uncommon in pediatric age group.